Audit Sistem Informasi Inventory Menggunakan Framework Cobit 5 - Fitria, Indah; Kurniawati, Laela; Haryanti, Tuti (LPPM Universitas Mulia, 2024)
PT Leea Footwear Indonesia is known as a company whose business activities focus on shoe production located in Tegal and has implemented an information system to support inventory management. However, companies often face obstacles such as data produced by information systems that are not suitable, which can cause delays in work processes and data accuracy. Therefore, an information system audit is needed to assess whether the procedures implemented are in accordance with established standards. The data collection method used in this research was interviews and questionnaires involving 11 respondents from PT Leea Indonesian Footwear. The questionnaire is designed to power the Cobit 5 framework based inventory system and is filled in by the concerned employees. The results of the analysis show that the average capability level of the inventory information system is at level 2 (Managed Process). This indicates that the company has managed the IT governance process, especially in the ERP-based inventory information system, well through continuous planning, evaluation and adjustment. The research results show that the highest level of ability is the MEA01 subdomain reaching 3.18 and the lowest is the DSS04 subdomain with a value of 1.24 and is still quite far from the target, namely at level 4, as well as other subdomains, namely DSS01, DSS02, DSS03, DSS05, DSS06, MEA02 and MEA03 still has not reached the target because there is still a GAP.